On Plato’s artistic definition of philosophy: the Dialogues as the highest form of poetry (Revista Archai, 2016)
This article tries to show how Plato conceived of his own philosophy as the highest form of poetry. In the first section, I briefly analyze in the first section three ancient testimonies (Aristotle, Longinus and Proclus) that already interpreted the Dialogues as a kind of poetry. Moreover, I comment on other modern authors that also recognized the literary aspects of Plato’s philosophy, although for a variety of reasons they never developed methodically this reading. In the second section, I show then how Plato comprehended his philosophy in Phaedon as well as in Phaedrus from an artistic perspective. Finally, I emphasize how his thought, contrary to what is normally believed, cannot be hostile to art.